Breaking the chains of isolation: A systematic review on family psychoeducation as a catalyst for social function improvement in schizophrenia - Steffiani, Laras; Keliat, Budi Anna; Hargiana, Giur (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: As a catalyst by accelerating social recovery through family empowerment, enabling long term functional improvement and triggering synergistic effects with other therapies, family psychoeducation (FPE) has been effective in reducing relapse rates and improving social functioning among individuals with schizophrenia. Purpose: To evaluate how FPE affected schizophrenic patients' social functioning and social isolation, especially in culturally diverse settings. Method: A systematic review of 10 articles (2015–2024) from PubMed, Sage Journals, and ScienceDirect was conducted. The studies encompassed randomized controlled trials, quasi-experimental approaches, and case series. Critical appraisal using JBI tools assessed risk of bias, with a focus on outcomes such as treatment adherence, social functioning, and hospitalization rates. FPE interventions improved treatment adherence, social functioning, and reduced social isolation in patients with schizophrenia. Results: FPE is effective in enhancing social functioning and mitigating isolation in schizophrenia, particularly when culturally adapted and integrated with multimodal therapies. Conclusion: While clinical symptom outcomes varied, FPE’s role in empowering families and enhancing community-based care is critical.